2020
DOI: 10.1186/s13756-020-00802-w
|View full text |Cite|
|
Sign up to set email alerts
|

Infection prevention knowledge, practice, and its associated factors among healthcare providers in primary healthcare unit of Wogdie District, Northeast Ethiopia, 2019: a cross-sectional study

Abstract: Background: Adequate knowledge and safe practice of infection prevention among healthcare providers are vital to prevent nosocomial infections. Thus, this study aimed to assess the level of knowledge and practices of healthcare providers towards infection prevention and its associated factors in the health facilities of Wogdie District, Northern Ethiopia. Methods: Institution based cross-sectional study was conducted among 171 healthcare providers who were selected by a simple random sampling technique. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 22 publications
4
39
2
Order By: Relevance
“…However, it is vital to acknowledge that almost all health professionals who took part in this study constantly wear personal protective equipment such as face mask/face shield at work and regularly practice good hand hygiene. Similar findings were reported in other developing countries namely Ethiopia, Nepal, and China [ 16-18 ]. Good hand hygiene practice and adherence to personal protective equipment were two of the most important preventive measure to repel nosocomial infection.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it is vital to acknowledge that almost all health professionals who took part in this study constantly wear personal protective equipment such as face mask/face shield at work and regularly practice good hand hygiene. Similar findings were reported in other developing countries namely Ethiopia, Nepal, and China [ 16-18 ]. Good hand hygiene practice and adherence to personal protective equipment were two of the most important preventive measure to repel nosocomial infection.…”
Section: Discussionsupporting
confidence: 90%
“…It is not surprising that the education level of healthcare workers did not influence COVID-19 preventive practice as studies in other developing countries reported similar findings [ 16 , 20 ]. The preventive practice among healthcare was also not influenced by their profession.…”
Section: Discussionmentioning
confidence: 60%
“…First, IPC training is often limited in LMICs. 24 25 A WHO survey of 88 countries to assess implementation of the WHO core components of an IPC programme found that only 54% had in-service IPC training. 26 Over half (18 of 32) of national nursing associations reported IPC training had not been provided within 6 months of the pandemic's start.…”
Section: Summary Boxmentioning
confidence: 99%
“…These findings showed an inverse association between IPC knowledge and proportion of COVID-19 infection that was statistically significant, this was in accordance with recent studies. [29][30][31][32] Regarding the HCWs' opinions about the high proportion of infection among them in Egypt, they thought this could be due to shortage of PPE (88.8%) inconsistent with recent studies, 9,25,33 work overload (84.2%) in agreement with recent studies 32 and lack of knowledge on how to use PPE as estimated by Houghton systematic review, 25,33 and the HCWs recommended raising the awareness for the importance of IPC (41.9%).…”
Section: Discussionmentioning
confidence: 99%